EXPLANATORY READING IN THE LIGHT OF APPRECIATION, IN THE ALMIGHTY’S SAYING {O PATIENCE IS MOST FITTING. AND ALLAH IS THE ONE SOUGHT FOR HELP AGAINST THAT WHICH YOU DESCRIBE} A SEMANTIC GRAMMATICAL STUDY - Alzughair, Khairallah Mahdi Jassim Muhammad (Journal of Learning on History and Social Sciences, 2024)
The research aims to clarify the effect of estimation in clarifying the interpretation of the Qur’anic text, as it has been observed that estimation determines the interpreter’s point of view in choosing the appropriate interpretation for this estimation. It has been noticed that some interpreters may go beyond what is compatible between estimation and interpretation, which prompted the research to clarify and guide these areas. Therefore, the research had its importance in referring to appreciation and its impact on the interpretive reading of the Qur’anic text. So in choosing AlMighty's saying “so patience is most fitting. And Allah is the one sought for help against that which you describe” (Yusuf: 18), was a clear example to explain what we referred to the tension between interpretation and appreciation, in both its grammatical and meaningful types. When choosing an estimate, the interpreter had to take into account the attachment of the appropriate meaning to this estimate, which generates cognitive agreement between the interpretive reading and the linguistic reading, to result in saying, through what we have referred to , the importance of regarding the estimate to be in its place. Because meaning represents the core of syntactic and semantic agreement and is the critical point that reveals the correctness of the semantic and syntactic structure according to the context. This is by describing the Qur’anic text as a context that must be read conveniently to appropriate it.